2003
DOI: 10.1097/00005176-200302000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Characterization, and Biologic Activity of Recombinant Human Lactoferrin in Rice

Abstract: The results indicate recombinant human lactoferrin has stability similar to native human lactoferrin when exposed to thermal treatment, pH treatment, and in vitro digestion, suggesting it may be active when added to infant formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 27 publications
5
58
1
2
Order By: Relevance
“…The other heat treatments applied to lactoferrin affected its antibacterial activity to different degrees depending on the bacterium, the more intense heat treatments of 72 C 10 min and 85 C 10 min affecting that activity to a greater extent. The results that we obtained are in agreement with those reported by Suzuki et al, 39) who found that 72 C for 20 s did not affect the antimicrobial activity of human lactoferrin or of the recombinant protein from rice against E. coli (EPEC). Moreover, it has also been observed in previous studies that the capacity of bovine lactoferrin to interact with different bacteria was unaffected by pasteurization (72 C, 15 s) and was reduced to a different degree by a UHT treatment.…”
Section: Effect Of Heat Treatment On the Antibacterial Activity Of Rhsupporting
confidence: 93%
“…The other heat treatments applied to lactoferrin affected its antibacterial activity to different degrees depending on the bacterium, the more intense heat treatments of 72 C 10 min and 85 C 10 min affecting that activity to a greater extent. The results that we obtained are in agreement with those reported by Suzuki et al, 39) who found that 72 C for 20 s did not affect the antimicrobial activity of human lactoferrin or of the recombinant protein from rice against E. coli (EPEC). Moreover, it has also been observed in previous studies that the capacity of bovine lactoferrin to interact with different bacteria was unaffected by pasteurization (72 C, 15 s) and was reduced to a different degree by a UHT treatment.…”
Section: Effect Of Heat Treatment On the Antibacterial Activity Of Rhsupporting
confidence: 93%
“…We therefore also used a "gastric" pH of 4 to evaluate this possibility. We have previously [46] used such a pH as an in vitro model to study protein digestion in infants, who have been shown to have a considerably higher stomach pH than adults [47]. Dietary factors (with the exception of tannic acid) demonstrated limited effects on Fe uptake from Ft digested at pH 4; however, following digestion at pH 2, pronounced effects of these factors on Fe uptake were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Ранее рекомбинантный лактоферрин человека полу-чали в различных системах: растениях, микроскопи-ческих грибах, с использованием молочных животных [64][65][66][67]. Рассматриваемый белок гликозилирован, поэ-тому лучшими его продуцентами являются млекопитаю-щие, в клетках которых имеется соответствующий меха-низм гликозилирования.…”
Section: лактоферрин -иммуногенный белок молокаunclassified